ACTIVATION OF INVESTMENT ACTIVITIES AT TRK ENTERPRISES - Іванов, Андрій; Ткаченко, Тетяна (SWorldJournal, 2025)
The article substantiates the theoretical and practical foundations for intensifying investment activity of enterprises in the tourism and recreation complex (TRC) of Ukraine through the prism of strategic management. The importance of developing effectiv